Exploring the diversity of urban and peri-urban agricultural systems in Sudano-Sahelian West Africa: An attempt towards a regional typology - Dossa, Luc Hippolyte; Abdulkadir, Aisha; AMADOU, Hamadoun; Schlecht, Eva (My University, 2011)
Developing appropriate and innovative technologies and policies to respond to the challenges that urban and peri-urban agriculture (UPA) faces in West Africa requires a better understanding of the existing production systems. Although there is an increasing recognition of the importance of UPA in the region, its extent, forms and related practices may vary across countries and cities because of different socio-economic conditions and urbanization patterns. A systematic classification of the regional UPA systems is lacking but is necessary to allow for meaningful comparisons between cities and avoid misleading generalizations. The purpose of this study was to develop a typology of UPA households across three selected West African cities. Survey data from 318 UPA households (Kano: 99, Bobo Dioulasso: 111, Sikasso: 108) were submitted to principal components analysis for categorical variables (CATPCA). Next, the Two-Step cluster method was used to classify the households using object scores obtained from the CATPCA. Diversification of farm activities, farm resource endowment and production orientation were the major discriminating variables. In each city, four distinct UPA systems were identified, of which three were common to Kano, Bobo Dioulasso and Sikasso: commercial gardening plus field crops and livestock (59%, 18%, and 37%), commercial livestock plus subsistence field cropping (14%, 41%, and 7%), and commercial gardening plus semi-commercial field cropping (14%, 28%, and 30%). The fourth group was different at each location and was characterized as follows: commercial gardening plus semi-commercial livestock in Kano (13%), commercial field cropping in Bobo Dioulasso (13%) and commercial gardening in Sikasso (26%).
Keywords: classification; systèmes de production agricole; élevage urbain et périurbain; Afrique de l'Ouest